1992
DOI: 10.1083/jcb.118.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular calcium signaling via gap junctions in glioma cells.

Abstract: Abstract. Calcium signaling in C6 glioma cells in culture was examined with digital fluorescence video microscopy. C6 cells express low levels of the gap junction protein connexin43 and have correspondingly weak gap junctional communication as evidenced by dye coupling (Naus, C. C. G., J. E Bechberger, S. Caveney, and J. X. Wilson. 1991. Neurosci. Lett. 126:33-36

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
168
2
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(179 citation statements)
references
References 27 publications
6
168
2
3
Order By: Relevance
“…Thus, the Ca 2+ responses in neighboring cells were primarily induced by Ca 2+ release via ATP-dependent generation of Ins(1,4,5)P 3 . Although in some cell types gap junctions reportedly contribute to the intercellular Ca 2+ wave in neighboring cells (Boitano et al, 1992;Charles et al, 1992;Felix et al, 1998;Hansen et al, 1995;Sneyd et al, 1995;StrahonjaPackard and Sanderson, 1999), the gap junction inhibitors 1-octanol and 16-DSA had no effect on Ca 2+ responses in neighboring cells in the present study. Given that intercellular Ca 2+ waves are mediated by released ATP, we anticipated that ATP would have autocrine actions on the mechanical-stimulation-induced Ins(1,4,5)P 3 generation and subsequent Ca 2+ release in stimulated cells.…”
Section: +contrasting
confidence: 46%
“…Thus, the Ca 2+ responses in neighboring cells were primarily induced by Ca 2+ release via ATP-dependent generation of Ins(1,4,5)P 3 . Although in some cell types gap junctions reportedly contribute to the intercellular Ca 2+ wave in neighboring cells (Boitano et al, 1992;Charles et al, 1992;Felix et al, 1998;Hansen et al, 1995;Sneyd et al, 1995;StrahonjaPackard and Sanderson, 1999), the gap junction inhibitors 1-octanol and 16-DSA had no effect on Ca 2+ responses in neighboring cells in the present study. Given that intercellular Ca 2+ waves are mediated by released ATP, we anticipated that ATP would have autocrine actions on the mechanical-stimulation-induced Ins(1,4,5)P 3 generation and subsequent Ca 2+ release in stimulated cells.…”
Section: +contrasting
confidence: 46%
“…Extracellular Ca 2ϩ and Mg 2ϩ may also be modulating these or other channels in astrocytes. However, the dependence of intercellular Ca 2ϩ signaling on both connexin expression and ATP release (Charles et al, 1992;Cotrina et al, 1998;Guthrie et al, 1999), as well as the effect of divalent cations on the flux of low-molecular-weight dyes (a characteristic property of connexin channels), is most directly explained by an effect of extracellular Ca 2ϩ and Mg 2ϩ on ATP release through connexin hemichannels. Release of other nucleotides through connexin hemichannels has also been found to be critically dependent on the extracellular concentrations of divalent cations (Bruzzone et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ waves in astrocytes have been shown to be dependent on both expression of connexins and on diffusion of an extracellular signaling molecule, namely ATP (Charles et al, 1992;Cotrina et al, 1998Cotrina et al, , 2000Guthrie et al, 1999). We and others have recently provided evidence for a mechanism that reconciles roles for both connexins and ATP release in astrocyte Ca 2ϩ signaling, i.e., release of ATP through connexin hemichannels (Cotrina et al, 1998;Stout et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…17,[39][40][41][42] When stimulated by an extracellular message, cells require direct communication between adjoining cells to promote rapid transmission of intercellular signals; that is, biologic signals are passed from stimulated cells to adjoining cells through GJIC. [43][44][45] Previous studies showed that disruption of GJIC between hepatocytes resulted in aberrant biologic signaling that contributed to neoplastic transformation and defective metabolic processes in vivo. 18,19 The vast majority of tumor promoters inhibit intercellular communication both in vivo [46][47][48][49] and in vitro, 8,46 and therefore, the modulation of gap junctional communication may play a role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%